2017
DOI: 10.4330/wjc.v9.i2.109
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance imaging assessment of outcomes in acute myocardial infarction

Abstract: Cardiovascular magnetic resonance (CMR) imaging uniquely characterizes myocardial and microvascular injury in acute myocardial infarction (AMI), providing powerful surrogate markers of outcomes. The last 10 years have seen an exponential increase in AMI studies utilizing CMR based endpoints. This article provides a contemporary, comprehensive review of the powerful role of CMR imaging in the assessment of outcomes in AMI. The theory, assessment techniques, chronology, importance in predicting left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 202 publications
(292 reference statements)
1
33
0
1
Order By: Relevance
“…ESVi decreased in IGF-1 MSPs group over the 10 weeks period, while it increased slightly in CON and remained stable in MSPs. These results, especially the one´s found in the IGF-1 MSPs group, agree with data described in literature that indicate that EDVi increases, ESVi decreases and compensatory hypertrophy of the remote myocardium are common findings after MI in order to preserve stroke volume and LVEF 44 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…ESVi decreased in IGF-1 MSPs group over the 10 weeks period, while it increased slightly in CON and remained stable in MSPs. These results, especially the one´s found in the IGF-1 MSPs group, agree with data described in literature that indicate that EDVi increases, ESVi decreases and compensatory hypertrophy of the remote myocardium are common findings after MI in order to preserve stroke volume and LVEF 44 .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, in this preclinical investigation, we used CMR for morphological and functional evaluation of the heart. This imaging technique is widely recommended for the assessment of IS and cardiac function [40][41][42][43][44] and offers a variety of parameters potentially suited as surrogate end-points in clinical studies 45 . In clinical research the most relevant parameter for assessing heart function is LVEF 42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute myocardial infarction (AMI) is a leading cause of death worldwide [1, 2]. Recent studies have found that stem cell transplantation is useful for treating myocardial infarction [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patient risk after an acute MI can be identified by multi-modality imaging approach with echocardiography, ventriculography, and/or Cardiacmagnetic Resonance (CMR) imaging.CMR has the unique ability to assess global and regional LV function post-MI, quantify infarct size with Late Gadolinium Enhancement (LGE), assess the status of the microvasculature by identifying Microvascular Obstruction (MO), and evaluate the area at risk with T2-weighted imaging of myocardial edema. Thus, CMR is uniquely positioned to evaluate the post-infarct patient [11] .…”
Section: Discussionmentioning
confidence: 99%